CHILDREN'S CAPABILITIES IN ISLAMIC RELIGIOUS EDUCATION THROUGH THE KKN PROGRAM OF UIN-SU STUDENTS IN TJ. IBUS VILLAGE - Fakira, Qania Athaya; Mayesti, Sabila Amelia; Rahmadani, Suci; Sabrina, Aura; Nuh, Muhammad (Academic Solution Publisher, 2024)
Tanjung Ibus Village, which is located in Secanggang District, Langkat Regency, is an area with a strong religious life. However, the challenges in spreading religious education in rural areas such as Tanjung Ibus cannot be ignored. Limited access to educational resources, a lack of competent teaching staff, and a lack of facilities and infrastructure for religious education are obstacles that are often faced. The North Sumatra State Islamic University (UIN-SU) Real Work Lecture Program (KKN) with group code 124 took the initiative to make a real contribution through teaching and learning activities in Tanjung Ibus Village. This program not only aims to improve children's academic abilities, but also to strengthen their understanding of the teachings of their religion. There are several programs offered by KKN 124 Uinsu, namely, Teaching at MDA and teaching the Qur’an. The KKN student teaching program helps increase children's Islamic religious knowledge in Tanjung Ibus Village. Through interactive and fun learning methods, children can more easily understand basic religious concepts such as monotheism, fiqh, morals and Islamic history.